Effects of chemical surface pretreatments on the surface roughness and shear bond strength of fiber post-resin cement interfaces: a preliminary in vitro study - Elif Turkes Basaran; Magrur Kazak; Kagan Gokce; Yasemin Benderli Gokce (PeerJ)
Background This preliminary study evaluates the impact of different chemical surface pretreatments on the surface roughness (Ra) of fiber posts and the shear bond strength (SBS) at the interface between the horizontal surface of fiber posts and resin cement, highlighting an area that has not been extensively researched. Methods Fifty glass fiber posts (Cytec Blanco, Hahnenkratt) were used, and polishing discs were employed to create a horizontally flat surface. Their dimensions were standardized using a digital caliper and divided into two pieces from each post (n = 20). The experimental groups included different pretreatment protocols: Group I (Control) had no pretreatment, Group II used 4% hydrofluoric acid (HF) (Porcelain Etchant, Bisco), Group III used 9.6% HF (Porcelain Etch Gel, Pulpdent), Group IV used 20% hydrogen peroxide (HP) (Merck KGaA), and Group V used 35% HP (Whiteness HP, FGM). Ten specimens from each pretreatment group were used for Ra evaluation (Perthometer Mahr), while the other ten were prepared for SBS testing. Silane and primer were applied before dual-cure resin cement (Multilink N, Ivoclar Vivadent), and SBS was tested after 48 h using a universal testing machine (Instron). SBS and Ra data were analyzed with one-way ANOVA and Tukey’s post hoc tests (p < 0.05). Results Statistical analysis revealed no significant pairwise differences when evaluating SBS values (p = 0.055). However, Groups IV and V exhibited higher SBS values compared to Groups I, II, and III. While 20% HP and 4% HF did not significantly enhance SBS, higher concentrations of HP achieved clinically acceptable bond strength. The surface pretreatment methods significantly influenced Ra (p = 0.00003). Groups III and IV exhibited significantly higher Ra values than Groups I, II, and V. Conclusion This preliminary study indicates that chemical surface pretreatments can be safely used to enhance the bond strength between fiber posts and resin cement, as they are not time-consuming, easy to use, and clinically applicable.